Peningkatan Kemampuan Membaca dan Menyimak dengan Menggunakan Metode Speed Reading pada Pembelajaran Bahasa Indonesia. - Billa Titania, Rizma; Bahtiar, Reza Syehma; Jarmani, Jarmani (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
The writing of this article aims to improve reading and listening skills by using the method of speed reading in Indonesian language learning in fifth-grade elementary school students because Indonesian is the language we use in everyday life, therefore learning Indonesian must be taught to children as early as possible so that children can know well about the language in their country. The methodology used in this paper is the method of studying literature or it can be called a literature review. This literature review is an important tool as a context review to assist authors in completing a study. The results of this literature study make students faster in reading because in the process of speed reading there are also listening skills that help students not to read many times so they can understand the contents of the reading and not waste a lot of time and can facilitate the teacher in delivering all information. The skills of reading, listening and speed reading are a unity that cannot be separated because they are interrelated with one another.Â Keywords: Reading, Listening, Speed Reading method, Indonesian.